(TO ROAM) IN SEARCH OF EMPOWERING PEDAGOGICAL THEORIES FOR LANGUAGES LEARNING: LESSONS LEARNED - Lesley Harbon (International Conference on Languages and Arts, 2013)
William Blake, one of England's greatest poets, the B52s, one of America's top rock bands of the 80s and 90s, and perhaps even the Minangkabau people through their merantau, all acknowledge in their own ways, that to “roam” can be a way to new learning. Blake stated, “How sweet I roam’d from field to field”, expressing the enjoyment of a journey. The B-52s, an American New Wave band, formed in the mid-1970s, sang about the joys of roaming “without wings, without wheels”. The Minangkabau people of West Sumatra encourage/expect their young men and women to roam in search of new knowledge and experiences, merantau, before eventually bringing their learning back home. In fact even modern telecommunications terminology uses the term “roaming”. A belief in the power of “roaming” to seek new truths has been a characteristic of the human journey for a very long time. For more than three decades, I myself have been fortunate enough to have had opportunities to roam in my own search for answers to questions about empowering theories for education in general, and languages education in particular. It is my belief that through the teaching and learning of languages and cultures we can engage with multiculturalism, social justice and inclusion in schools which are in themselves contributing issues adding to the complexity and richness of our society. What I have learned while I roamed about different education systems is that there is generally a deep desire to make schools a better place. Education does this by dividing up the curriculum into subject areas. One such subject area is foreign language education. Yet empowering theories for languages education are not always in evidence and making schools and universities better places may well just be serendipitous, rather than a result of good planning. This paper examines why we want (and need) to empower the individuals in our schools and universities, what it might look like to empower language teachers and students through an intercultural orientation, and how dialogue and reflexivity are crucial as we continue to roam.